Diagnosis dan Tata Laksana Post-Traumatic Stress Disorder: Tinjauan Pustaka - Susanto, Wenly (Cermin Dunia Kedokteran, 2025)
Post-traumatic stress disorder (PTSD) is a stress disorder that can disrupt social life due to cognitive and mood changes. The etiology of PTSD involves a combination of biological, psychological, and social factors, which interact to cause post-traumatic stress disorder. Biological factors such as genetics also play a role. Exposure to traumatic stressors in PTSD needs to be distinguished from ordinary stressors. According to the DSM-V, the diagnostic criteria for PTSD for adults, adolescents, and children over 6 years of age consist of criterion A (stressor), criterion B (intrusive symptoms), criterion C (avoidance symptoms), criterion D (changes in negative cognition and mood), criterion E (changes in reactivity and vigilance), criterion F (symptom duration), and criteria G and H. Diagnosis of PTSD is a challenge in medical practice. PTSD treatment consists of psychotherapy and pharmacotherapy. Psychotherapy is considered more efective but requires a longer time commitment, so maintaining patient engagement is crucial to improving prognosis. Appropriate management can help reduce PTSD symptoms.